2012
DOI: 10.1074/jbc.m111.285601
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Human RNA Polymerase III Transcription by DNMT1 and DNMT3a DNA Methyltransferases

Abstract: Background: Human small nuclear RNA genes exhibit powerful transcription potential. Results: The DNMT1 and DNMT3a DNA methyltransferases down-regulate snRNA transcription by RNA polymerase III. The RB tumor suppressor facilitates DNMT promoter recruitment. Conclusion: Human RNA polymerase III transcription is regulated by epigenetic modification. Significance: This study uncovers a novel relationship between DNA methyltransferases and RB for epigenetic regulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 62 publications
3
28
0
Order By: Relevance
“…In agreement with our results, U6 snRNA family genes, which are transcribed by RNA polymerase III, have been reported to be regulated by DNA methylation recently [26]. Increased expression of RNA polymerase III products is often observed in transformed cells [27].…”
Section: Resultssupporting
confidence: 92%
“…In agreement with our results, U6 snRNA family genes, which are transcribed by RNA polymerase III, have been reported to be regulated by DNA methylation recently [26]. Increased expression of RNA polymerase III products is often observed in transformed cells [27].…”
Section: Resultssupporting
confidence: 92%
“…In this scenario, RB positioned distally to the nucleosome would similarly be brought into position to its targets within the core machinery by DNA wrapping. Consistent with the involvement of chromatinmodifying factors in RB regulation of Pol II transcription, RB expression by transient transfection facilitated DNMT1 recruitment to the RNU6-1 locus [116], suggesting that this and other chromatin modifying factors contribute to Pol III regulation during tumor suppression, a topic for future efforts. Together, these studies have uncovered an unanticipated diversity of RB tumor suppressor function in the control of Pol III.…”
Section: Genome-wide Analyses Of Rb and Rna Polymerase IIImentioning
confidence: 76%
“…Thus, we sought to determine if there were additional mechanisms regulating U6 expression, in addition to decreased p53 expression levels (Figure 3B). Previous experiments in breast cancer cell lines have demonstrated that U6 promoter methylation can be regulated by DNMTs [30], suggesting that U6 transcription may be regulated by epigenetic changes. Previously, the methylation status of the U6 promoter has not been determined in normal liver tissue from male C57BL/6J mice.…”
Section: Resultsmentioning
confidence: 99%